Alternate Reality Games: A Transformational Design for Teaching Children’s Literature and 21st Century Skills - Moula Evangelia; Konstantinos Malafantis (Recent Research Advances in Arts and Social Studies Vol. 6, 2024)
This study presents the process of the transformational design of a young adult novel into an alternate reality game (ARG) for educational purposes, creating this way, an affinity space for students. This project adds value since, despite ARGs’ prior use in education, the relevant literature does not support the notion of a transformational process of this kind. Design concerns, the primary attributes of ARGs, the standards and driving forces behind successful ARGs, as well as the project’s inherent constraints. The project was applied to the Greek young adult novel: Leros’ Code by Kostas Stoforos [47] and the derivative ARG was implemented during the 2018-19 school year in secondary education students in Rhodes, Greece as part of a postdoctoral research (ongoing). The project’s goal was to examine how an ARG could be compatible with the literary curriculum and the teaching mechanics and even more, how it could promote collaborative learning and literacy practices of the 21st century. This article presents the transformational design as dictated by the relevant literature and does not include the results of the implementation. Its implementation in an extra-curricular time-zone, as a supervised and coordinated by a teacher activity, deprived it at the beginning of a significant, potential part of the fascination about the unknown and the charm of participating in a real mystery.